Ameliorative Effect of Javiscum® and Ficus Exasperata on Nw – Nitro- L-Arginine Methyl Ester (L-Name)-Induced Dyslipidemia in Wistar Rats (2022)
The term "cardiovascular diseases" (CVDs) refers to a variety of heart and blood vessel conditions. It is the main factor in close to 30% of all fatalities worldwide and the leading cause of morbidity and mortality. CVDs have emerged as an important health problem all over the world but the dependence on conventional drugs for management has been plagued with toxicity and inconsistency as side effects while alternative intervention is gradually gaining acceptance. Hence the present work sought to compare and evaluate the effects of methanol extract of Javiscum®(JV), a polyherbal formulation and a single herbal formulation Ficus exasperata (FE) on serum lipids, and liver enzymes of Nw –nitro- L-arginine methyl ester (L-NAME) treated rats. Adult male Wistar rats were grouped into 9 (n=6). Control group I was administered distilled water. Group II, with L-NAME (40 mg/kg body weight), group III, L-NAME and amlodipine 5 mg/kg per body weight while groups IV, V, VI were administered L-NAME (40 mg/kg) and treated with 400, 200, 100 mg/kg of JV. Groups VII, VIII and IX were administered L-NAME (40 mg/kg) and treated with 400, 200, and 100 mg/kg of FE extract respectively. Animals were weighed, and blood samples, collected after 28 days after models from previous researchers. The lipid profile, serum nitric oxide and liver enzyme levels, were evaluated by standard methods. L-NAME was observed to reduce body weights, nitric oxide concentration and High-density lipoprotein (HDLc), but increased liver enzymes Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), total cholesterol and triglycerides. JV at 400 mg/kg elicited the highest reversal of L-NAME effects on nitric oxide level. JV and FE at 200 mg/kg were able to significantly (p˂ 0.05) reduce the concentration of AST when compared to L-NAME treated group. 2 F. exasperata and Javiscum®, reversed the negative effects of L-NAME, thereby validating the use of these herbals in CVD management. The activities of JV and FE revealed that a polyherbal formulation may not necessarily confer a more significant activity as generally believed. Isolation and characterisation of the constituents responsible for activities may be templates for newer CVD drug discovery.